KADAR ABU, BETN, DAN SERAT IKAN CAKALANG ASAP DENGAN PERENDAMAN EKSTRAK DAUN BELIMBING WULUH - Ida Astuti; Asniati Ningsi (Fapetrik-UMPAR, 2019)
Gorontalo Province is one of the regions that have the biggest potential to produce skipjack fish (Katsuwonus pelamis) in Indonesia. The community processes the catch into processed which has economic value, both traditional and modern. One of them is smoked fish which gives a distinctive taste and can extend its shelf life and maintain nutrient levels. The purpose of this study was to determine the effect of wealth starfruit leaf extract on Proximate Cakalang fish smoke. This research is an experimental study with the treatment of using star fruit leaf extract (EDBW) and without star fruit leaf extract (TEDBW) with 3 replications. The parameters tested were proximate (ash, fiber, and BETN). The results of the analysis were calculated using Anova Two-Factor with Replication. The results showed that the ash of skipjack smoked fish with EDBW treatment was 1.55% and without EDBW treatment was 1.33%, BETN with EDBW treatment was 0.73% and without EDBW treatment was 1.37%, fiber content with EDBW treatment was 0.08% and without treatment, EDBW is 0.23%. The best result is this belimbing leaf extract capable of lowering BETN by 0.64%. It can be concluded that the starfruit leaf extract significantly affects BETN and fiber but does not affect the ash content.